2014
DOI: 10.1007/s10681-014-1324-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability for total phenolics, flavonoids and antioxidant activity of testaless seeds of a peanut recombinant inbred line population and identification of their controlling QTLs

Abstract: Peanut, an important oil producing crop contains bioactive compounds like phenolics and flavonoids which determine its antioxidative activity. We report here the genetic variability for total phenolics, flavonoids and DPPH radical scavenging activity of testaless seeds of a peanut recombinant inbred line population. On an average, the population contained 1.65 mg GAE/g and 240 lg CE/g of phenolics and flavonoids, respectively in its seed. The DPPH radical scavenging activity of this population ranged from 1.27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Hassan et al (2016) transformated chitinase gene into peanut to enhance resistance to leaf spot. A RIL population was also used for the initial location of QTLs for peanut TFC by Mondal et al (2015), but further research on this topic is required.…”
Section: Hou Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Hassan et al (2016) transformated chitinase gene into peanut to enhance resistance to leaf spot. A RIL population was also used for the initial location of QTLs for peanut TFC by Mondal et al (2015), but further research on this topic is required.…”
Section: Hou Et Almentioning
confidence: 99%
“…On the basis of 50 extant QTLs for isoflavone in soybean, Wang et al (2015) located 21 new QTLs using a RIL population, including many sites related to the environment. In peanut, Mondal et al (2015) located five QTLs for flavonoid content using a RIL population, including pPGPseq_12A07-UBC 841, GM 633-Ah242, RM14E11-TE 389, ARS 796-SSR_HO115593, and S89-TC11D09, with a minimum distance between markers of 21.0 cM. In this study, 215 pairs of EST-SSR markers were used to determine genetic differences in the 57 accessions.…”
Section: Hou Et Almentioning
confidence: 99%
“…In recent years, QTLs associated with economically important traits such as disease resistance [8, 9], drought tolerance [10, 11], seed and oil quality [12, 13], agronomic and yield traits [14, 15] were identified in peanut crop. Molecular markers tightly linked to QTLs after validation can be further deployed in GAB [5, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported 30 major QTLs for saturated fatty acids (Wang et al 2015). In addition to this, ten major QTLs were reported with the PVE% range 12.5, 25-67 and 11.5-33 for the total phenolics, total flavonoids and DPPH radical scavenging, respectively by the Mondal et al (2015). The linked markers are available for use in breeding to improve the fatty acid profiles in peanut.…”
Section: Oil and Nutritional Qualitymentioning
confidence: 87%
“…In peanut, ICRISAT with the research partners has done pioneer work to identify linked markers for drought tolerance related traits. In this context, major QTLs were identified successfully for transpiration (5 QTLs), transpiration efficiency (4 QTLs), carbon discrimination ratio (1 QTL), specific leaf area (6 QTLs), leaf area (1 QTL), SPAD chlorophyll Mondal et al (2015) metre reading (SCMR) (12 QTLs), biomass (3 QTLs), shoot dry weight (2 QTLs), haulm weight (1 QTL), harvest index (1 QTL), canopy conductance (3 QTLs) and total dry matter (1 QTL) (Varshney et al 2009b;Ravi et al 2011;Gautami et al 2012a). The another study while dissecting drought tolerance traits Fonceka et al (2012) identified two major QTLs each for 100 pod weight, 100 seed weight, haulm weight, pod number, total biomass, STI-100 pod weight, STI-100 seed weight, STI-haulm weight, STI-pod number, STI-total biomass, one major QTL each for STI-pod weight, STI-seed number and STI-seed weight.…”
Section: Trait Mapping Through Linkage Mappingmentioning
confidence: 99%